1969
DOI: 10.1139/v69-725
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanum ion catalysis of nucleophilic displacement reactions of monoesters of methyl phosphonic acid

Abstract: The catalytic effects of lanthanum ion on the rate of hydrolysis of p-nitrophenyl hydrogen methylphosphonate in aqileous solution at pH >7.0 are reported. Increases in rate by a factor of about 3.6 x lo4 have been observed. No such catalysis was found for diesters of methylphosphonic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1971
1971
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Although ammines of Cu and other transition metals are commonly used, we concentrated on using lanthanum ions, for which a considerable acceleration comparable with the ferment effect on the reaction under study was found in our and other publications. [39][40][41][42][43][44][45]68 The kinetics of hydrolysis of 1 and 2 and also the pH changes of the PEI solution with lanthanum ion concentration are plotted in Figures 6-9 for the PEI-800-La(III) and PEI-50-La(III) systems. The results obtained for the PEI-25-La(III) system are similar to those for the PEI-50 based solution; therefore, only the latter are discussed here as an example.…”
Section: Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ammines of Cu and other transition metals are commonly used, we concentrated on using lanthanum ions, for which a considerable acceleration comparable with the ferment effect on the reaction under study was found in our and other publications. [39][40][41][42][43][44][45]68 The kinetics of hydrolysis of 1 and 2 and also the pH changes of the PEI solution with lanthanum ion concentration are plotted in Figures 6-9 for the PEI-800-La(III) and PEI-50-La(III) systems. The results obtained for the PEI-25-La(III) system are similar to those for the PEI-50 based solution; therefore, only the latter are discussed here as an example.…”
Section: Sectionmentioning
confidence: 99%
“…PEI is known to accelerate the hydrolysis of phosphorus acid esters via general basic catalysis. , Besides, it contributes to the catalysis of the reaction due to the sorption of reagents and to the formation of the substrate−polymer catalytic complex. The modification of the system with La(III) ions makes it possible for the electrophilic catalysis to contribute to the catalytic mechanism, since a considerable acceleration of nucleophilic substitution at phosphorus by lanthanum ions is well-known. The addition of sodium dodecyl sulfate (SDS) to the systems opens up additional opportunities for binding the reagent due to the solubilization mechanism together with the sorption pattern.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This value was calculated on the basis of the data in the literature (ref ) using the p K a value of 9.06 for H 2 O ligated to La 3+ .…”
Section: Referencesmentioning
confidence: 99%
“…Various nucleophiles have been examined as hydrolytic reagents toward PNPMP, including hydroperoxide, hydroxamate, fluoride, thiophenylate, and hypochlorite; hydroperoxide ( k 2 = 2.6 × 10 -3 M -1 s -1 at 30 °C) was the most reactive species . Metal cation mediated cleavage of PNPMP was observed with Ca 2+ (12-fold acceleration), whereas La 3+ , the pyridine-2-carbaldehyde oxime chelate of Y 3+ (acting as a polymeric hydrate), and the 1,1,2,2-tetramethyl-1,2-diaminoethane chelate of Co(III) each afforded very substantial rate accelerations with this substrate . Additionally, La 3+ cations enhanced the hydrolysis of PNPPP ( 4 ) 100-fold (pH 7.4, 60 °C), whereas the transition metal cations Cu 2+ , Ni 2+ , and Zn 2+ were ineffective …”
Section: Introductionmentioning
confidence: 99%